2021
DOI: 10.1136/neurintsurg-2021-017956
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained early neurological deterioration after endovascular treatment for acute large vessel occlusion: incidence, predictors, and clinical impact: Data from ANGEL-ACT registry

Abstract: BackgroundEarly neurological deterioration (END) may occur in some patients with acute large vessel occlusion (LVO) undergoing endovascular treatment (EVT). Despite several clear causes of END, such as symptomatic intracranial hemorrhage, failure of recanalization, and intraprocedure complications, a particular END, termed unexplained END (ENDunexplained), exists. We aimed to investigate the incidence, independent predictors, and clinical impact of ENDunexplained after EVT in patients with acute LVO.MethodsSub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…In this scenario, the risk/benefit balance of EVT in mild LVO seems not favourable. It is worth noting that, beside obvious causes, END after EVT may remain unexplained (UnEND); interestingly, two recent studies on LVO AIS found that UnEND after EVT was independently associated with low initial NIHSS score [38,39]. These findings suggest that patients with mild symptoms may be at increased risk of UnEND after EVT and our results may support this hypothesis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this scenario, the risk/benefit balance of EVT in mild LVO seems not favourable. It is worth noting that, beside obvious causes, END after EVT may remain unexplained (UnEND); interestingly, two recent studies on LVO AIS found that UnEND after EVT was independently associated with low initial NIHSS score [38,39]. These findings suggest that patients with mild symptoms may be at increased risk of UnEND after EVT and our results may support this hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…One possible explanation may be related to higher rates of non‐haemorrhagic END in the IVT + EVT group. END is reported after EVT and is associated with poor outcome [36–39]. Beside SICH, other obvious causes of EVT‐related END can only partially be addressed; intra‐procedural complications may therefore partially explain our findings.…”
Section: Discussionmentioning
confidence: 79%
“…8 Many groups adopted these diagnostic criteria for ICAD-LVO in clinical practice with subsequent studies. 3 9 10 11 12 However, in other studies, 50% was the cut-off value for the degree of fixed stenosis in the diagnosis of ICAD-LVO after MT. 13 14 15 16 Some studies also considered fixed stenosis degree < 50% but with flow and perfusion impairment on angiography or evidence of reocclusive tendency after MT as ICAD-LVO.…”
Section: Diagnostic Criteria Of Icad-lvomentioning
confidence: 82%
“…A high NLR is associated with an intense inflammatory reaction 16. When AIS occurs, the immune system is activated, lymphocytes are suppressed by systemic stress, and neutrophils migrate to the ischemic area 17. Then, the serum neutrophil counts increase, whereas lymphocyte counts decrease over time in patients undergoing EVT 18.…”
Section: Discussionmentioning
confidence: 99%